유기물 반도체 Pentacene에서 전자와 정공의 전도 특성 연구 - 임상빈 (The Graduate School, Ajou University, 2005)
The transport properties of electron and hole in pentacene organic thin-film transistor are studied. The transport properties of electrons and holes were could be observed by using not ordinary planar structure but special step structure. And the characteristics of step structure are verified by using commercial simulation program ATLAS. Through the 0.8μm-long pentacene organic thin-film transistor (OTFT) either p-type or n-type behaviour could be observed under different gate and drain voltage conditions. Current-voltage characteristics reveal that positive gate voltages increase the drain current, when the lower contact is operated as drain electrode, indicating electron transport through the channel. Through the simulations we could knows that the asymmetric structure of our device enabled stronger electric field at a negative voltage contact, which helped electron injection into pentacene. And we also investigates defect concentration effects to the characteristics of step structure. In conclusion, we could observe n-type transfer characteristics in pentacene which known as p-type semiconductor.
학위논문(석사)--아주대학교 대학원 :전자공학과,2005